BIOLOGICAL AND SYNTHETIC MESH USE IN RECONSTRUCTIVE SURGERY IN PATIENTS WITH BREAST CANCER - M. V. Ermoshchenkova (Issledovaniâ i Praktika v Medicine, 2017)
Introduction. In recent years, considerable success has been achieved in complex and combined treatment of breast cancer (BC). Reconstructive plastic surgery plays an important role in the rehabilitation of patients with breast cancer and it is currently considered as the causal treatment of mental disorders caused by loss of femininity and integrity of one’s own body. One-step breast reconstruction for cancer treatment makes it possible to use supplementary materials — synthetic and biological implants that can replace muscle autografts and thereby reduce trauma, blood loss, operation time, and thereby help to avoid the defect of donor areas. The authors describe the state of the art at present and demonstrate the results of their own research.Materials and methods. The object of study was 38 of breast cancer cases and 1 case of multiple gelioma caused by silicone implant rupture. 44 operations have been completed: 21 — radical subcutaneous mastectomy, 1 — subcutaneous mastectomy, 17 — skin-sparing radical mastectomy with one-step reconstruction with mesh implant (12 — titanium, 16 — polyester), 11 — acellular dermal matrix Permacol, 5 — prophylactic contralateral subcutaneous mastectomy with one-step reconstruction with silicone implant and a mesh implant due to a mutation of the BRCA1 gene. The technique of operations and the results of studies have been described in detail.Results. In the late post-operational period, the implants were removed in 5 cases: in 2 patients due to the development of inflammation of ADM, 3 — in connection with the development of bedsores and diastasis of the skin in the wound area when synthetic implants were used. From the total number of patients in the group (n = 39) excellent cosmetic results were reported in 21 cases (54%), good — in 13 (33%) and unsatisfactory — in 5 (13%) cases due to the removal of the implants.Conclusions. Biological and synthetic materials are significantly important options for breast reconstruction. They are adequate substitutes for autologous muscle flaps if the patients for the operation are properly select.